HEART TRANSPLANTATION WITH EXTREMELY EXTENDED COLD ISCHEMIA TIME OF THE DONOR HEART - S. A. Alsov; A. V. Fomichev; D. V. Doronin; V. A. Shmyrev; D. E. Osipov; A. M. Chernyavskiy (Вестник трансплантологии и искусственных органов)
Heart transplantation is the gold standard for the treatment of terminal heart failure. The main method of the donor heart preservation is cold perfusion. The recommended maximum time for cold ischemia of the donor heart is 240 minutes. Exceeding this safe limit increases the risk of postoperative allograft dysfunction and death. However, there are reports positing a possibility to prolong the time of ischemia of the donor heart without a signifi cant risk of complications. The article presents the experience of successful transplantation of the donor heart with the cold ischemia time was 440 minutes.